Fecal Shedding of Multidrug Resistant Escherichia coli Isolates in Dogs Fed with Raw Meat-Based Diets in Brazil - Carolina Pantuzza Ramos; Carolina Yumi Iceri Kamei; Flávia Mello Viegas; Jonata de Melo Barbieri; João Luís Reis Cunha; Yaovi Mahuton Gildas Hounmanou; Fernanda Morcatti Coura; Jordana Almeida Santana; Francisco Carlos Faria Lobato; Anders Miki Bojesen; Rodrigo Otávio Silveira Silva (MDPI AG, 2022)
The practice of feeding dogs raw meat-based diets (RMBDs) is growing in several countries, and the risks associated with the ingestion of pathogenic and antimicrobial-resistant Escherichia coli in dogs fed these diets are largely unknown. We characterized E. coli strains isolated from dogs fed either an RMBD or a conventional dry feed, according to the phylogroup, virulence genes, and antimicrobial susceptibility profiles of the bacteria. Two hundred and sixteen E. coli strains were isolated. Dogs fed RMBDs shed E. coli strains from the phylogroup E more frequently and were positive for the E. coli heat-stable enterotoxin 1-encoding gene. Isolates from RMBD-fed dogs were also frequently positive for multidrug-resistant E. coli isolates including extended-spectrum beta-lactamase (ESBL) producers. Whole-genome sequencing of seven ESBL-producing E. coli strains revealed that they predominantly harbored blaCTX-M-55, and two strains were also positive for the colistin-resistant gene mcr-1. These results suggest that feeding an RMBD can affect the dog's microbiota, change the frequency of certain phylogroups, and increase the shedding of diarrheagenic E. coli. Also, feeding an RMBD seemed to be linked with the fecal shedding of multidrug-resistant E. coli, including the spread of strains harboring mobilizable colistin resistance and ESBL genes. This finding is of concern for both animal and human health.